Programs and Policies that Promote Positive Youth Development and Prevent Risky Behaviors : An International Perspective - Naudeau, S. (2012)
This chapter provides an international perspective on the promotion of positive development and the prevention of risky behavior among youth. We discuss some of the specific challenges that youth face in low- and middle-income countries and identify six key evidence-based policies and programs that aim to promote positive youth development and prevent risky behavior. We also propose a set of practical recommendations for policymakers and other stakeholders on how to develop and implement an effective youth portfolio in the context of limited financial resources.